The impact of dividend policy on price-to-earnings ratio: The case of Western Europe - Simona Nikolovska (Journal of Contemporary Economic and Business Issues, 2020)
In a world full of studies dealing with the relationship of price-to-earnings ratio and the dividend payout ratio, rarely noticeable are those examining the possibility that this relationship may be non-linear. Although rare, studies that aim to fill this gap focus solely on the US capital market. The lack of those kinds of studies alongside with the absence of studies for Europe was main incentive for this paper. Therefore this paper aims to examine the conditional and nonlinear relationship between price-to earnings ratio and dividend payout ratio where by the inclusion of various factors the non/linear relationship is conditioned on the comparative levels of return on equity and the required rate of return. In order to explore this relationship, a fixed effects panel regression model is used. Main findings are based on an examination of an annual data of 69 companies from 11 European countries in the period from 2014 to 2018. The results show positive relationship and convexity between the price-to-earnings ratio and the dividend payout ratio, leading to the conclusion that European investors prefer dividends and "award" the increase in the dividend payout with increased price to- earnings ratio.
Keywords: C33; G12; G32; G35; 330; dividend payout ratio; price-to-earnings ratio; nonlinearity; convexity; capital market